2023
DOI: 10.1155/2023/5486017
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Mechanism of Yifei-Sanjie Pill in Cancer-Related Fatigue

Abstract: Background. The incidence of cancer-related fatigue (CRF) is increasing, but its lack of clear pathogenesis makes its prevention and treatment difficult. Therefore, it is of great significance to clarify the pathogenesis of CRF and find effective methods to treat it. Methods. The CRF model was established by intraperitoneal injection of LLC cells in ICR mice to explore the pathogenesis of CRF and verify the therapeutic effect of the Yifei-Sanjie pill (YFSJ). The active components of YFSJ were found by LC/MS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, both pieces of information were input into the molecular docking module of TCMNPAS to analyze the binding affinity of quercetin towards Akt1. The results demonstrated a strong binding affinity of − 8.9 kJ/mol, indicating a favorable interaction between quercetin and Akt1 [61].…”
Section: Molecular Dockingmentioning
confidence: 97%
“…Subsequently, both pieces of information were input into the molecular docking module of TCMNPAS to analyze the binding affinity of quercetin towards Akt1. The results demonstrated a strong binding affinity of − 8.9 kJ/mol, indicating a favorable interaction between quercetin and Akt1 [61].…”
Section: Molecular Dockingmentioning
confidence: 97%
“…In a case control study of 376 NSCLC patients, it was found that YFSJF plus chemotherapy improves the median overall survival compared with chemotherapy alone 12 . Additional clinical research shown that YFSJF with chemotherapy could improve quality of life and lessen fatigue 13,14 . Nevertheless, the pharmacological mechanisms of YFSJF in lung cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additional clinical research shown that YFSJF with chemotherapy could improve quality of life and lessen fatigue. 13,14 Nevertheless, the pharmacological mechanisms of YFSJF in lung cancer remain poorly understood.…”
mentioning
confidence: 99%